EVALUASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING PADA SISWA KELAS X SMA NEGERI KOTA JAMBI - Harman Harman (Universitas Batanghari Jambi, 2018)
This study aims to determine the ability of solving mathematical problems through creative problem solving learning model higher than the direct learning model on the students of class X state senior high school of Jambi city. This research is an experimental research because of causal relationship. The way this study is to compare one or more comparison group that have received treatment. The sample of this research is class X MIA 1 as experiment class which is taught by creative problem solving model, while control class is X MIA 2 which is taught by direct learning model. From the result of research and discussion that have been done can be concluded that the ability of solving mathematical problems of students who are studied through the creative problem solving (experiments) learning model obtained an average of 71,9 and students in the learning through direct learning model (control) average 63,3. Of the two clasess obtained tcount is 4,17 and ttable is 1,66 then in this case H0 is rejected and H1 accepted at 95% confidence level. Then it can be concluded that the problem solving ability of mathematical students taught through creative problem solving learning model is higher that the students taught through direct learning model in class X state senior high school of Jambi city.Keywords: Mathematical Problem Solving Ability, Creative Problem Solving Learning Model, Direct Learning Model.